(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the economic basis of diversion of Siberian rivers. Considering climate change, water scarcity and environmental problems in Central Asia, the effectiveness of water transfer projects from Siberia has been studied.